PEMAHAMAN, KESADARAN , SANKSI PAJAK, PELAYANAN FISKUS, E-FILLING SYSTEM DAN KEPATUHAN WAJIB PAJAK: UNDERSTANDING OF TAXPAYERS, TAXPAYER AWARENESS, TAX PENALTIES, FISCAL SERVICES, AND E-FILLING SYSTEMS AND THE COMPLIANCE OF INDIVIDUAL TAXPAYERS - Karsam, Karsam; Sasmita, Djenni; Dewi, Susana; Solihin, Solihin; Tedja, Bambang; Ksp, Agnes (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
Low tax compliance, has an impact on state revenues. Therefore the government has taken various ways to improve tax compliance. The purpose of this study determinedness-Filling systems, tax penalties, Fiscal Services, taxpayer awareness, and understanding of taxpayers have significant influences on the compliance of individuals taxpayer registered with the Jakarta Tax Office either partially or simultaneously. Data were obtained from 120 respondents who were registered as individuals taxpayer at Jakarta Tax Office. By using multiple linear regression techniques, the result of the study shows that the e-Filling system, tax penalties, tax services, taxpayer awareness, and the understanding of taxpayers have positive and significant effects on the compliance of individuals taxpayer registered with the Jakarta Tax Office.